IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DI DESA SUMBERGONDO KECAMATAN GLENMORE KABUPATEN BANYUWANGI TAHUN 2015 - Basuki, Andik; Sasongko, Sasongko; Sunarko, Bagus Sigit (Universitas Muhammadiyah Jember, 2018)
AbstractImplementation of ADD policies, by making development programs, and community empowerment integrated with the APBDes program. The ADD program planning is carried out in a participatory manner along with the APBDes planning by involving the community through the musrenbangdes. Even reporting on the use of ADD funds is done simultaneously with the APBDes reporting. Meanwhile, this study found that the success of implementing ADD policies is determined by the content and context of the policies and implementers who implement the ADD program. In addition, the success of policy implementation also looks at the impact on the community as a policy target group.Key words: Implementation ofÂ ADD policy